Establece relaciones espaciales con su cuerpo y los objetos - Huerta Guillermo, Giovany Consuelo (2018)
This is a work in which it deals with the Notion of Space and constitutes the logical mathematical framework that should serve to structure the future abstract-formal thinking of the chid under twelve years of age. Therefore it is very important that the Initial Education Teachers must it respecting their process according to the age of the child and fulfill this activity by selecting the teaching strategies and learning activities that encourage the development of the topological notions, projective and euclidian that guarantee in the future, the understanding of the fundamental principles of Geometry.